Modeling the relationship of the TPACK framework with cyber wellness, school climate, and digital nativity of basic education teachers - Valle, Lislee C.; Gonzales, Roselyn R.; Almacen, Rose Mary L.; Batucan, Gesselle; Gonzales, Gamaliel G. (Frontiers in Education, 2024)
In the ever-evolving landscape of educational technology, it is vital to understand the empirical relationships of teachers' Technological Pedagogical and Content Knowledge (TPACK) and its interplay with explanatory factors such as cyber wellness, school climate, and digital nativity. This study employs Covariance-Based Structural Equation Modeling (CB-SEM) to analyze selfreported data from 311 basic education teachers in Central Visayas, Philippines. The model demonstrates robust validity and reliability, showing diverse direct impacts on the antecedent variables to the seven constructs of TPACK. The findings reveal sixteen significant hypothesized paths, with digital nativity has a significant effect on all three core knowledge domains of TPACK while school climate and cyber wellness have a significant effect on two knowledge domains. Another significant finding shows that content knowledge emerged with the highest significant effect on technological content knowledge (𝛽 = 0.621). This connection highlights the fundamental role of content knowledge in successfully integrating technological competencies among teachers, especially from a developing economy. The study provides policy insights tailored to post-pandemic educational management.